Academic Senate Minutes 2010-02-25 - Academic Senate:::::::::
Approval of Agenda. Chair Report. President Report. Provost Report. Vice President of Administration and Finance Report. Special Visit: Dean Mark Merickel, Extended Education. Vice President of SAEM Report. Associated Students Report. Chair-Elect Report. Proceeding with Election approved. Statewide Senator Report. CFA Report. EPC Report. FSAC Report. Resolution from SBC: Resolution to Spend 55% of Funding in the Academic Schools - Second Reading – Approved. Resolution in Support of Retention of Santa Rosa City Schools Librarians Approved.